Wasting Time as a Cultural Practice in Contemporary Serbia - Bojan Žikić (Etnoantropološki Problemi)
The expression "wasting time" is a colloquial label for periods of time spent waiting to receive services in various social situations in which people find themselves in state or private institutions, such as the Ministry of Internal Affairs or health institutions, banks and technical inspections of vehicles, etc. In this way, the superiority of social or cultural time over individual time is manifested. Cultural use of time represents the tendency to manage linear time by repeating events anchored in certain time segments, such as rituals, music festivals, sports events, or national holidays. Individuals perceive time based on cultural learning, understanding sociocultural time as a framework for organizing their personal time. This means that when they are not engaged in activities arising from collective time, individuals tend to organize their time according to their personal needs and intentions - as much as possible.Wasting time is therefore perceived as time not spent on activities related to work or free time that are the consequence of personal choice or existential necessity. The term most often refers to the waiting periods, which are apparently not regarded as integral to completing a task, such as a medical examination or obtaining personal documents. The concept of wasting time emerges as an uncreative, imposed, wasted time spent on completing tasks that could be organized differently. It is an empty time, devoid of important events and which is contrasted with periods of activity. The idea of ​​wasting time corresponds to the personal experience of time. The given expression is a consequence of evaluating whether or not a certain period of time was spent usefully, viewed from a personal perspective. Everyone's experience suggests that time seems to pass more slowly when we can do nothing but wait. The networking of such experiences, arising from a multitude of social situations that impose prolonged waiting as a procedural part to obtain what is considered useful or necessary for individuals, can be characterised as a cultural practice. The contributors to this practice include all social institutions that provide services to users through direct contact and hold a societal monopoly of performing their activities.